Foreign worker remittance and risk of regional economy: a preliminary study on the oil palm plantation sector in the east coast of Sabah, Malaysia - Wan Shawaluddin Wan Hassan; Ahmad Mosfi Mahmood; Muhammad Syarafi; Alzubair Rijal (National Crisis & Emergency Management Research Institute, 2013)
As a considerably largest industry in Sabah, the oil palm plantation sector has been contributing significantly to the state economy. The sector is also notable for hiring the considerably huge number of foreign workers, with the approximation of more than 80 percent of foreign workers involved in the oil palm industry. The heavy reliance on foreign workers is associated to the large remittance outflow from Malaysia. This paper aims to descriptively analyze the demographic and socioeconomics of foreign workers in oil palm plantation sector on remittances. About 30 foreign workers participated in this study through convenience sampling. The study concludes that the demographic and socioeconomic characteristics are significant in explaining the pattern, decisions and motivations for sending money to the homeland.